Body macronutrient composition is predicted by lipid and not protein content of the diet. Issue 23 (22nd October 2017) - Moatt, Joshua P.; Hambly, Catherine; Heap, Elizabeth; Kramer, Anna; Moon, Fiona; Speakman, John R.; Walling, Craig A.
Abstract: Diet is an important determinant of fitness‐related traits including growth, reproduction, and survival. Recent work has suggested that variation in protein:lipid ratio and particularly the amount of protein in the diet is a key nutritional parameter. However, the traits that mediate the link between dietary macronutrient ratio and fitness‐related traits are less well understood. An obvious candidate is body composition, given its well‐known link to health. Here, we investigate the relationship between dietary and body macronutrient composition using a first‐generation laboratory population of a freshwater fish, the three‐spine stickleback ( Gasterosteus aculeatus ). Carbohydrate is relatively unimportant in the diet of predatory fish, facilitating the exploration of how dietary protein‐to‐lipid ratio affects their relative deposition in the body. We find a significant effect of lipid intake, rather than protein, on body protein:lipid ratio. Importantly, this was not a result of absorbing macronutrients in relation to their relative abundance in the diet, as the carcass protein:lipid ratios differed from those of the diets, with ratios usually lower in the body than in the diet. This indicates that individuals can moderate their utilization, or uptake, of ingested macronutrients to reach a target balance within the body. We found no effect of diet on swimming endurance, activity, or testes size. However, there was an effect of weight on testes size, with larger males having larger testes. Our results provide evidence for the adjustment of body protein:lipid ratio away from that of the diet. As dietary lipid intake was the key determinant of body composition, we suggest this occurs via metabolism of excess protein, which conflicts with the predictions of the protein leverage hypothesis. These results could imply that the conversion and excretion of protein is one of the causes of the survival costs associated with high‐protein diets. Abstract : Traits that mediate the link between dietary macronutrient intake and fitness‐related traits are poorly understood, though an obvious candidate is body composition. Here, we show that lipid intake, not protein, predicts body composition and importantly the ratio of protein:lipid in the carcass does not match that of the diet. Our results could imply that the conversion and excretion of protein is one of the causes of the survival costs associated with high‐protein diets.